UMP Holdings and Yayasan UMP help affected communities - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 19 January 2021 - Sympathise with those affected by the floods, many parties extended assistance by donating various necessities for the flood victims in Pahang.